A study on the suitability of the PTW microDiamond detector for kilovoltage x-ray beam dosimetry. (May 2018) - Damodar, Joshita; Odgers, David; Pope, Dane; Hill, Robin
Abstract: Kilovoltage x-ray beams are widely used in treating skin cancers and in biological irradiators. In this work, we have evaluated four dosimeters (ionization chambers and solid state detectors) in their suitability for relative dosimetry of kilovoltage x-ray beams in the energy range of 50 – 280 kVp. The solid state detectors, which have not been investigated with low energy x-rays, were the PTW 60019 microDiamond synthetic diamond detector and the PTW 60012 diode. The two ionization chambers used were the PTW Advanced Markus parallel plate chamber and the PTW PinPoint small volume chamber. For each of the dosimeters, percentage depth doses were measured in water over the full range of x-ray beams and for field sizes ranging from 2 cm diameter to 12 × 12 cm. In addition, depth doses were measured for a narrow aperture (7 mm diameter) using the PTW microDiamond detector. For comparison, the measured data was compared with Monte Carlo calculated doses using the EGSnrc Monte Carlo package. The depth dose results indicate that the Advanced Markus parallel plate and PinPoint ionization chambers were suitable for depth dose measurements in the beam quality range with an uncertainty of less than 3%, including in the regions closer to the surface of the water as compared with Monte Carlo depth dose data for all six energy beams. The response of the PTW Diode E detector was accurate to within 4% for all field sizes in the energy range of 50–125 kVp but showed larger variations for higher energies of up to 12% with the 12 × 12 cm field size. In comparison, the microDiamond detector had good agreement over all energies for both smaller and larger field sizes generally within 1% as compared to the Advanced Markus chamber field and Monte Carlo calculations. The only exceptions were in measuring the dose at the surface of the water phantom where larger differences were found. For the 7 mm diameter field, the agreement between the microDiamond detector and Monte Carlo calculations was good being better than 1% except at the surface. Based on these results, the PTW microDiamond detector has shown to be a suitable detector for relative dosimetry of low energy x-ray beams over a wide range of x-ray beam energies. Highlights: The PTW microDiamond detector and 60012 electron diode have been evaluated for kilovoltage x-ray beam dosimetry. The microDiamond detector produced accurate doses for all energies and field sizes including very small fields. The diode detector is only suitable for lower energy x-ray beams and smaller field sizes.